THU0108 Different Performance of the Major Disease Activity Measures ASDAS and BASDAI in Patients with Axial Spondyloarthritis Treated with Non-Steroidal Anti-Inflammatory Agents (NSAIDS) – Results from A Prospective Study. (10th June 2014) - Baraliakos, X.; Kiltz, U.; Heldmann, F.; Appel, H.; Dybowski, F.; Igelmann, M.; Kalthoff, L.; Krause, D.; Menne, H.-J.; Saracbasi, E.; Schmitz-Bortz, E.; Braun, J.
Abstract : Background: Measures for disease activity (BASDAI, ASDAS) are routinely used in patients (pts) with axial spondyloarthritis (axSpA). The ASDAS, a composite score that includes clinical measures and CRP, has high discriminatory capacity for assessment of disease activity. Clinical trial data showed that the ASDAS has a better sensitivity to change than the BASDAI in pts treated with TNF-blockers. However, there are no data on the comparison of ASDAS and BASDAI in axSpA pts treated with NSAIDs, which are recommended as first choice prior to a possible initiation of TNF-blockers. Objectives: We compared the performance of BASDAI and ASDAS in assessing and predicting clinical response to intensive NSAID treatment in axSpA pts with high disease activity. Methods: Consecutive pts with nr-axSpA and AS (n=50 each group) were included in a prospective study if their BASDAI level was ≥4, if they had not yet received the maximally approved dose of NSAIDs and if they had not been treated with anti-TNF agents to date. After inclusion the maximal dose of NSAIDs was administered over one week (wk) and the dose was then reduced in case of BASDAI <4 or, in case of BASDAI ≥4, the NSAID was changed and pts were treated for another 3 wks at maximal doses. Clinical and laboratory parameters were assessed and the dosage of NSAIDs was quantified by using the ASAS-index. Data were collected before (BL) and after 1 and 4 wks of NSAID treatment. Results: Baseline characteristics of AS and nr-axSpA patients were similar. Prior to treatment, an ASDAS >2.1 was found in 74% and 76% of pts with AS and nr-axSpA, respectively. There was a significant decrease in both, ASDAS (BL: 2.5±0.6, 1wk: 1.9±0.8, 4wk: 1.6±0.8) and BASDAI (BL: 5.8±1.3 1wk: 4.1±2.1 4wk: 2.1±3.1). At wks 1 and 4, a BASDAI <3 was achieved by 20% and 22% of AS and 15% and 18% of nr-axSpA pts, respectively. An ASDAS <2.1 was reached by 29% and 34% of AS and 34% and 33% of nr-axSpA pts, respectively. An ASDAS <1.3 indicative of inactive disease was found in 13% and 16% of AS and 15% and 18% of nr-axSpA pts, respectively. However, at wk 4 a BASDAI ≥4 was still present in 34% axSpA pts, but only 15% of these had an ASDAS <2.1. Another 33% of pts had an ASDAS <2.1 but only 4% of those had a BASDAI <4. This difference was much more prominent in nr-axSpA patients (Table). In the univariate logistic regression analysis both, ASDAS (OR: 3.6, p=0.002) and BASDAI (OR: 1.8, p=0.001) predicted the eligibility for anti-TNF therapy after 4wk of NSAIDs at BL, ASDAS performed superior to BASDAI. Conclusions: BASDAI and ASDAS showed a similar magnitude of response on NSAID treatment in both AS and nr-axSpA. Of interest, the discriminative power of the ASDAS was much clearer in patients classified as nr-axSpA and especially in those who could be considered as candidates for anti-TNF treatment. These data challenge the concept of only using the BASDAI cut-off ≥4 for such treatment decisions. Disclosure of Interest: : None declared DOI: 10.1136/annrheumdis-2014-eular.6086